2016
DOI: 10.1017/dmp.2015.190
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution of Disaster-Specific Emergency Department Use After Hurricane Sandy in New York City

Abstract: Objective: We aimed to characterize the geographic distribution of post-Hurricane Sandy emergency department use in administrative flood evacuation zones of New York City. Methods: Using emergency claims data, we identified significant deviations in emergency department use after Hurricane Sandy. Using time-series analysis, we analyzed the frequency of visits for specific conditions and comorbidities to identify medically vulnerable populations who developed acute postdisaster medical needs. Results: We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…3 More surprisingly, however, we also found a statistically significant posthurricane increase in ED visits with a primary or secondary diagnosis code of homelessness. 3 Indeed, homelessness emerged above most medical conditions as having one of the strongest and most persistent increases in ED diagnoses comparing the weeks pre-and post-Sandy's landfall. 3 It is well known that natural disasters can cause people to lose their homes, leading to increases in homelessness.…”
Section: Introductionmentioning
confidence: 50%
See 3 more Smart Citations
“…3 More surprisingly, however, we also found a statistically significant posthurricane increase in ED visits with a primary or secondary diagnosis code of homelessness. 3 Indeed, homelessness emerged above most medical conditions as having one of the strongest and most persistent increases in ED diagnoses comparing the weeks pre-and post-Sandy's landfall. 3 It is well known that natural disasters can cause people to lose their homes, leading to increases in homelessness.…”
Section: Introductionmentioning
confidence: 50%
“…3 We found a number of primary medical diagnoses driving this increased ED use, such as renal conditions including dialysis dependence, respiratory conditions including chronic obstructive pulmonary disease and ventilator dependence, and diabetes. 3 More surprisingly, however, we also found a statistically significant posthurricane increase in ED visits with a primary or secondary diagnosis code of homelessness. 3 Indeed, homelessness emerged above most medical conditions as having one of the strongest and most persistent increases in ED diagnoses comparing the weeks pre-and post-Sandy's landfall.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…study, screening for conditions that demonstrated increased postdisaster use of emergency care, we found that there was also a statistically significant increase in the number of New York City emergency department (ED) patients presenting with a primary or secondary diagnosis of diabetes even in the first week after Hurricane Sandy. 9 These findings require additional investigation as to which characteristics make certain diabetic patients at higher risk for needing acute medical care after a disaster. The goal of this study was to identify salient patient characteristics that increase the likelihood that a diabetic patient will develop acute medical needs after a disaster such as Hurricane Sandy.…”
Section: Introductionmentioning
confidence: 99%